Weighted variable Hardy spaces on domains - Melkemi, Oussama; Saibi, Khedoudj; Mokhtari, Zouhir (Advances in Operator Theory, 2021)
In this paper, we introduce and study the weighted variable Hardy space on domains. We prove the atomic decompositions of this space, and as application, we figure out its dual space.